Reliable and Energy Efficient Protocol for MANET Multicasting - Bander H. AlQarni; Ahmad S. AlMogren (Journal of Computer Networks and Communications)
A mobile ad hoc network (MANET) consists of a self-configured set of portable mobile nodes without any central infrastructure to regulate traffic in the network. These networks present problems such as lack of congestion control, reliability, and energy consumption. In this paper, we present a new model for MANET multicasting called Reliable and Energy Efficient Protocol Depending on Distance and Remaining Energy (REEDDRE). Our proposal is based on a tone system to provide more efficiency and better performance, and it combines solutions over the Medium Access Control (MAC) layer. The protocol consists of a new construction method for mobile nodes using a clustering approach that depends on distance and remaining energy to provide more stability and to reduce energy consumption. In addition, we propose an adjustment to the typical multicast flow by adding unicast links between clusters. We further present in our model a technique to provide more reliability based on a busy tone system (RMBTM) to reduce excessive control overhead caused by control packets in error recovery. We simulate our proposal using OPNET, and the results show enhancement in terms of reliability, packet delivery ratio (PDR), energy consumption, and throughput.